Technological modernization in window restoration: integration of 3D printing and digital modeling - Klykailo, Vitalii (Global Prosperity, 2026)
Abstract. Digital technologies are currently being actively integrated into design and construction practices. The process involves collecting and accumulating the necessary information, ensuring its orderliness and timely updating in accordance with the technical and managerial tasks to be solved at individual stages of the object's life cycle: during design, construction or reconstruction, and during further operation. This approach contributes to a significant increase in resource management efficiency and comprehensive safety in the field of construction and restoration. The purpose of the study is to analyze the potential of modern digital technologies in the restoration and manufacture of non-standard parts. In particular, the study examines the possibilities of 3D printing technologies for replacing elements of old structures, defines printing technology, and provides examples of the use of structures in real life. The potential for using BIM modeling for work planning is studied. The study identifies the main advantages of introducing digital technologies in the architectural and construction sphere, including acceleration of design and construction processes, project development and implementation; reduction of errors and shortcomings, improvement of design quality and accuracy, minimizing resources for corrections. The study highlights the main functions of BIM modeling and additive manufacturing in the context of improving characteristics, reproducing models of complex geometry, and simplifying the manufacture of individual elements of window structures during building restoration. It has been proven that the digitalization of the construction and architecture sector, which includes digital modeling and additive manufacturing, opens up wide opportunities for the potential development of the industry and its technological upgrade.